Ethics in Pediatric Trials - Chowdhury, Pranab Kumar; Dutta, Pradip Kumar; Mahmood, Nasruddin; Dutta, Asok Kumar (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7682 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):66-69